SISTEM KEKERABATAN MASYARAKAT NEGERI TULEHU - Gazali Rahman (TAHKIM, 2018)
The kinship relationship in the life of indigenous peoples in Tulehu country is manifested in three customary activities, namely marriage custom, adoption and division of inheritance and corpse. The marriage customs of the Tulehu peoples are acculturation with the teachings of Islam. In the marriage custom there are brothers who are similar to the hakam in Islamic teachings. According to Tulehu country customs of adopted children are entitled to the inheritance of their adoptive parents if adopted by foster parents of the family's own party. But the adopted child does not get an inheritance if adopted by foster parents from the family's own family or who has no family relationship at all. The people of Tulehu also have the custom of gotong royong (gathering of grief money) to help the family of the dead.